2019
DOI: 10.1002/pchj.290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hormonal alterations in major depressive disorder: A clinical study

Abstract: Major depressive disorder (MDD) is a severe mood disorder that may lead to use of drugs, alcohol, and even suicide in acute cases. It has been shown that neurotransmitters and hormones have the same receptors and pathways in the mood area of the brain. Therefore, metabolic and biochemical changes are expected in MDD and, in such diseases, understanding the hormonal alterations would be extremely helpful in the management or treatment with hormone replacement therapy. We evaluated levels of cortisol, adrenocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Our results suggest that serum FT4 and FT3 levels among SI with MDD were significantly lower than those among non-SI, and these results are consistent with those of previous studies. 18,28 Why FT3 and FT4 are related to SI? The dysregulation of serotonergic has been widely studied in adults and has been postulated as a biological marker for suicide.…”
Section: Risk Factors Of Si Among Mddmentioning
confidence: 99%
“…Our results suggest that serum FT4 and FT3 levels among SI with MDD were significantly lower than those among non-SI, and these results are consistent with those of previous studies. 18,28 Why FT3 and FT4 are related to SI? The dysregulation of serotonergic has been widely studied in adults and has been postulated as a biological marker for suicide.…”
Section: Risk Factors Of Si Among Mddmentioning
confidence: 99%
“…This author also observes an association with other disorders such as generalized anxiety, social phobia, and agoraphobia (Giltay et al, 2012). Likewise, a recent clinical study found decreased testosterone levels in both men and women with major depression compared to healthy participants (Asadikaram et al, 2019). Although most studies agree that low testosterone levels in men are related to depression (Ford et al, 2016;Kische et al, 2018;Zarrouf, Artz, Griffith, Sirbu, & Kommor, 2009), findings for women are inconsistent (Kische et al, 2018;Milman, Sammel, Barnhart, Freeman, & Dokras, 2015) and appear to depend on the woman's reproductive stage (Fiacco, Walther, & Ehlert, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…In relation to the metabolic effects of testosterone, it has been observed that they depend on a person's sex and stage of development. In women, they predispose to obesity and type 2 diabetes, either by increasing adiposity and insulin resistance, increasing food consumption or decreasing energy expenditure (Morford & Mauvais-Jarvis, 2016;Asadikaram et al, 2019). Chronic androgenic excess appears to alter metabolic pathways in women.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important signs of hormonal irregularity is sudden anxiety or depression. Depression is the most common psychiatric disorder and has recently been associated with hormonal imbalances (17). Today, depression is a serious and widespread problem (18).…”
Section: Introductionmentioning
confidence: 99%